Long-Term Results of Cementless Total Hip Arthroplasty Using a Modular Stem in Patients with Femoral Head Osteonecrosis - Kim, Hyun-Ho; Lim, Jung-Won; Jung, Young-Bok; Lee, Young-Kyun; Ha, Yong-Chan; Koo, Kyung-Hoi (The Journal of Hip Surgery, 2017)
Patients with femoral head osteonecrosis are younger and more active than those with osteoarthritis of the hip. More than 10-year results of total hip arthroplasty (THA) using modular cementless stem in osteonecrotic patients have not yet been reported. We determined clinical and radiologic results of cementless modular stem in a consecutive series of patients with femoral head osteonecrosis a minimum follow-up of 10 years. We retrospectively reviewed 48 patients (58 hips) who underwent THA for femoral head osteonecrosis with a cementless modular femoral stem. Metal-on-metal articulation was used in 32 hips and ceramic-on-ceramic articulation in 26. There were 26 men and 22 women with a mean age of 52 years at the time of the operation. These patients were followed for 10 to 15 years. All of the acetabular cups and femoral stems had radiographic evidence of bone ingrown stability at the final follow-up. Three hips were revised due to infection. There were no revisions for ceramic fracture or adverse reaction to metal debris. The survival rate was 94.8% (95% confidence interval: 89.8–100%). However, 12 patients (12 hips, 21%) suffered thigh pain. In six patients (six hips), the pain disappeared within 1 to 2 years, whereas the pain persisted until the final follow-up in the remaining six patients. As of 10 to 15 year, radiologic results and survival of THA using a modular femoral stem were good in patients with osteonecrosis. However, the incidence of thigh pain remains a matter of concern.
Keywords: osteonecrosis; cementless total hip arthroplasty; S-ROM